Jaundice As a Presentation of Thyrotoxic Crisis - Habib, Shah Khaled; Khan, Mohammad Ashik Imran; Mahbub, Md Shahriar; Rashid, MA; Miah, Md Titu; Gupta, Ratan Das; Alam, Md Billal (Journal of Medicine, 2011)
Thyrotoxic crisis is a life threatening condition which requires urgent detection and management. Due to its wide variety of presentation its diagnosis can be difficult in some cases and high index of suspicion is required for its diagnosis. We report a case of 45 year old lady presenting with fever, jaundice and passage of loose stool whose thyroid hormone profile proved her to be suffering from thyrotoxic crisis. Keyword: Thyrotoxic crisis; Jaundice; Antithyroid drugs; Hypoxia DOI: 10.3329/jom.v12i1.6935 J Medicine 2011; 12 : 70-72